Ochrona materiałów z dochodzeń lotniczych przed nieograniczonym wykorzystaniem procesowym: [Restrictions on use of aircraft accident and incident investigation materials in administrative and court proceedings] (Studia Prawnicze / The Legal Studies, 2012)
Zasadnicze rozważania w niniejszym artykule odnoszą się do ochrony materiału zgromadzonego w dochodzeniach lotniczych cywilnych. Jednakże na płaszczyźnie krajowej kwestie te unormowane są częściowo tymi samymi przepisami w odniesieniu do obu rodzajów lotnictwa. Dlatego wiele tez zawartych w tym artykule znajdzie także zastosowanie do materiałów zgromadzonych w postępowaniach KBWLLP.Nie istnieją co prawda przepisy, które zakładałyby bezpośrednio, że materiały zgromadzone w dochodzeniach lotniczych stanowią samodzielną podstawę rozstrzygnięć w innych postępowaniach lub takie, które obligowałyby jakiekolwiek organy do wykorzystania procesowego takich materiałów The article discusses the issue of records collected in aircraft accidents and incidents investigations in regard to their use in other procedures. The author summarizes the present state of international, European and national air law relating to protection of safety investigation records. Manner in which such information may be used in particular proceedings is mentioned first. Further, the author presents directions of use of the records, as well as axiology of record protection and premises of their authorized disclosure. The text includes remarks concerning implementation of international and European rules in Poland and proposals de lege ferenda. Besides that, the author points out the differences as to the status of records gathered in civil and state safety investigations.